Regulation of transcriptional silencing and chromodomain protein localization at centromeric heterochromatin by histone H3 tyrosine 41 phosphorylation in fission yeast. Issue 1 (10th November 2017) - Ren, Bingbing; Tan, Hwei Ling; Nguyen, Thi Thuy Trang; Sayed, Ahmed Mahmoud Mohammed; Li, Ying; Mok, Yu-Keung; Yang, Henry; Chen, Ee Sin
Abstract: Heterochromatin silencing is critical for genomic integrity and cell survival. It is orchestrated by chromodomain (CD)-containing proteins that bind to methylated histone H3 lysine 9 (H3K9me), a hallmark of heterochromatin. Here, we show that phosphorylation of tyrosine 41 (H3Y41p)—a novel histone H3 modification—participates in the regulation of heterochromatin in fission yeast. We show that a loss-of-function mutant of H3Y41 can suppress heterochromatin de-silencing in the centromere and subtelomere repeat regions, suggesting a de-silencing role for H3Y41p on heterochromatin. Furthermore, we show both in vitro and in vivo that H3Y41p differentially regulates two CD-containing proteins without the change in the level of H3K9 methylation: it promotes the binding of Chp1 to histone H3 and the exclusion of Swi6. H3Y41p is preferentially enriched on centromeric heterochromatin during M- to early S phase, which coincides with the localization switch of Swi6/Chp1. The loss-of-function H3Y41 mutant could suppress the hypersensitivity of the RNAi mutants towards hydroxyurea (HU), which arrests replication in S phase. Overall, we describe H3Y41p as a novel histone modification that differentially regulates heterochromatin silencing in fission yeast via the binding of CD-containing proteins.